1993
DOI: 10.1021/j100137a019
|View full text |Cite
|
Sign up to set email alerts
|

Branching ratio of the reaction amidogen + nitric oxide at elevated temperatures

Abstract: The branching ratios into the O H and H 2 0 producing channels in the reaction of NH2 with N O have been measured at four temperatures ranging from room temperature to 900 O C . The reaction was initiated by production of NH2 by excimer laser photolysis of ammonia at 193 nm in the presence of nitric oxide and was probed using a color center laser in conjunction with fast IR detectors. Upon photolysis, the NH3 infrared absorption decreases with consequent appearance of NH2 infrared absorption lines. The magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 9 publications
6
81
1
Order By: Relevance
“…For the overall process to be self-sustainable, it is required that the branching fraction of the NH 2 + NO reaction, defined as α = k 15 / (k 14 + k 15 ) must be at least 25% [1]. While early experiments [4,6] indicated a smaller branching fraction, it is now well established that α in the 1100-1400 K range attains values of 0.3 to 0.4 [12,16,22].…”
Section: The Thermal Deno X Processmentioning
confidence: 99%
See 1 more Smart Citation
“…For the overall process to be self-sustainable, it is required that the branching fraction of the NH 2 + NO reaction, defined as α = k 15 / (k 14 + k 15 ) must be at least 25% [1]. While early experiments [4,6] indicated a smaller branching fraction, it is now well established that α in the 1100-1400 K range attains values of 0.3 to 0.4 [12,16,22].…”
Section: The Thermal Deno X Processmentioning
confidence: 99%
“…Subsequent work, e.g. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], has confirmed that NNH (or N 2 + H) is indeed formed in the NH 2 + NO reaction, and modeling studies have identified it as a key intermediate in Thermal DeNO x [9,[19][20][21][22][23], where NH 3 is used as a reducing agent for selective non-catalytic reduction of NO.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5] Numerous investigations for the reaction system have been carried out via direct kinetic measurements, [6][7][8][9][10][11][12] high temperature kinetic modeling, 4,[13][14][15][16][17] ab initio/molecular orbital ͑MO͒ theory, [18][19][20][21][22][23] and Rice-Ramsperger-Kassel-Marcus ͑RRKM͒ calculations. 11,19,24,25 In view of the thermochemistry for the system, three exit channels may be involved in the reaction mechanism according to their reaction enthalpies,…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] For this reason, it has been the focus of much attention experimentally [7][8][9]12,[14][15][16][17] in recent years. However, the comparison between the temperature dependence of ␣ measured from direct laser kinetic studies and that measured indirectly from high temperature flame modeling still remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Elimination to form OH + HN 2 can occur at any point along the surface. While results from early studies on the branching ratio for OH formation differ significantly, the most recent studies (Hall et al,Dolson [405], Silver and Kolb [1188], Atakan et al, Stephens et al [1236], Park and Lin [1036]) agree on a value around 0.1 at 300 K, with N 2 +H 2 O making up the balance. (Table: 97-4, Note: 97-4) Back to Table C28.…”
Section: -41mentioning
confidence: 99%